Sirt1 Activation by Post-ischemic Treatment With Lumbrokinase Protects Against Myocardial Ischemia-Reperfusion Injury - Wang, Yi-Hsin; Li, Shun-An; Huang, Chao-Hsin; Su, Hsing-Hui; Chen, Yi-Hung; Chang, Jinghua T.; Huang, Shiang-Suo (Frontiers in Pharmacology, 2018)
Lumbrokinase is used as an oral supplement to support and maintain healthy cardiovascular function, and to treat cardiovascular diseases in clinical for more than ten years. Up until now, the mechanism of the cardioprotective effects of post-ischemic treatment with lumbrokinase has remained unclear. We therefore investigated the signaling pathways involved in the amelioration of myocardial ischemia-reperfusion (I-R) injury in rats treated with lumbrokinase 20 min after myocardial ischemia. Compared to vehicle-treated rats, post-ischemic treatment with lumbrokinase was associated with significant reductions in myocardial I-R-induced arrhythmias and myocardial damage, and an improvement in cardiac function. Moreover, lumbrokinase significantly upregulated levels of silent information regulator 1 (Sirt1). In addition, lumbrokinase significantly increased manganese-dependent superoxide dismutase (MnSOD) expression, decreased Cleaved-Caspase-3 expression, and induced deacetylation of FoxO1. On the other hand, lumbrokinase also significantly downregulated levels of succinate dehydrogenase (SDH), cytochrome c oxidase (CcO), nuclear factor kappa B (NF-κB) and elevated levels of microtubule-associated protein light chain 3 (LC3). Notably, the cardioprotective effects of lumbrokinase were abolished by administration of the specific Sirt1 inhibitor EX527. These findings demonstrate that post-ischemic treatment with lumbrokinase attenuates myocardial I-R injury through the activation of Sirt1 signaling, and thus enhances autophagic flux and reduces I-R-induced oxidative damage, inflammation and apoptosis.